Propagación clonal in vitro de anturio anthurium andreanum através de callo ú organogénesis indirecta - Espinoza Velepucha, Andrea Fernanda (2014)
In the biotechnology laboratory of the Faculty of Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala, research on the in vitro multiplication of Anthurrium andraeanum Lind from explants disinfected with mixtures of organic fungicides leaves leading to reduce problems was performed pollution caused by fungi and bacteria.The objectives were:1. Obtain the induction of somatic embryogenesis in Anthurium andreanum.2. Determine which treatment is best for highest percentage of embryogenic callus of Anthurium andreanum.The study leaves of anthurium, fungicides, Betadine, Rydomil, Phyton, Kasumin and disinfectants, sodium hypochlorite, sodium hidróxido, used glass bottles Stove, Balance, Beakers 50 ML, Fridge laminar flow chamber Autoclave, 25 ounce plastic tubs, disinfection Strips, Tags. The treatments were, T1. Solution sodium hydroxide Ridomil + Witness sodium hypochlorite solution, T2. Betadine Solution rydomil + + + Python + Kasumin sodium hydroxide, T3. Solution Kasumin + + Python + sodium hydroxide solution phyton + T4 + Kasumin sodium hydroxide, T5. Kasumin + sodium hydroxide, T6. Sodium hydroxide T7.Betadine. T8. Rydomil, T9. Phyton and T10. Kasumin.The studied variables, Percentage of contamination at 30 days, 45 days somatic embryogenesis, and 62 days, callus size, color of the callus. For the choice of explants young leaves with about 50 was used at 70% of normal size range "Sonata washed with liquid soap and water cleaning limbo gently with a sponge to remove dust and impurities, after this is the place in running water to remove soap residue. The material is then moved to the laminar flow chamber clarines solution was immersed gently shaking; in this phase disinfection nine treatments evaluated, for once disinfected leaves, cut into segments of about 1 cm 2 and finally introduce in vitro culture medium. From the analysis of variance was evident that disinfectants treatments, the best results in the protection of the in vitro culture of explants and I were alone and Rydomil Kasumin variable sodium hydroxide in which high statistical significance was obtained. Explants from young leaves free mother plants of good vegetative and free development of virus and disease was a suitable method for the development of embryogenesis starting point for the regeneration of Anthurium andreanum Lind; elected for the control of contamination of the culture medium of the explant Phyton fungicides anthurium was significantly similar to one mixtures Kasumin Phyton-sodium-hydroxide-sodium hydroxide Rydomil. They correspond to the formation of somatic embryos events no significant difference between treatments was obtained in the absence of statistical significance obtained for treatments.